MOLECULAR IMAGING OF PROSTATE CANCER: translating molecular biology approaches into the clinical realm - Vargas, Hebert Alberto (Eur Radiol, 2015)
The epidemiology of prostate cancer has dramatically changed since the introduction of prostate-specific antigen (PSA) screening in the 1980’s. Most prostate cancers today are detected at early stages of the disease and are considered “indolent”, however some patients’ prostate cancers demonstrate a more aggressive behavior which leads to rapid progression and death. Increasing understanding of the biology underlying the heterogeneity that characterizes this disease has lead to a continuously evolving role of imaging in the management of prostate cancer. Functional and metabolic imaging techniques are gaining importance as the impact on the therapeutic paradigm has shifted from structural tumor detection alone to distinguishing patients with indolent tumors that can be managed conservatively (e.g., by active surveillance) from patients with more aggressive tumors that may require definitive treatment with surgery or radiation. In this review, we discuss advanced imaging techniques that allow direct visualization of molecular interactions relevant to prostate cancer and their potential for translation to the clinical setting in the near future. The potential use of imaging to follow molecular events during drug therapy as well as the use of imaging agents for therapeutic purposes will also be discussed.